Risk factors and outcomes of lower respiratory tract infections after traumatic brain injury: a retrospective observational study - Caceres, Eder; Olivella, Juan C.; Yanez, Miguel; Viñan, Emilio; Estupiñan, Laura; Boada, Natalia; Martin-Loeches, Ignacio; Reyes, Luis Felipe (Frontiers in Medicine, 2023)
Background Traumatic brain injury (TBI) is a public health problem with a high burden in terms of disability and death. Infections are a common complication, with respiratory infections being the most frequent. Most available studies have addressed the impact of ventilator-associated pneumonia (VAP) after TBI; therefore, we aim to characterize the hospital impact of a broader entity, lower respiratory tract infections (LRTIs). Methods This observational, retrospective, single-center cohort study describes the clinical features and risk factors associated with LRTIs in patients with TBI admitted to an intensive care unit (ICU). We used bivariate and multivariate logistic regressions to identify the risk factors associated with developing LRTI and determine its impact on hospital mortality. Results We included 291 patients, of whom 77% (225/291) were men. The median (IQR) age was 38 years (28–52 years). The most common cause of injury was road traffic accidents 72% (210/291), followed by falls 18% (52/291) and assault at 3% (9/291). The median (IQR) Glasgow Coma Scale (GCS) score on admission was 9 (6–14), and 47% (136/291) were classified as severe TBI, 13% (37/291) as moderate TBI, and 40% (114/291) as mild TBI. The median (IQR) injury severity score (ISS) was 24 (16–30). Nearly 48% (141/291) of patients presented at least one infection during hospitalization, and from those, 77% (109/141) were classified as LRTIs, which included tracheitis 55% (61/109), ventilator-associated pneumonia (VAP) 34% (37/109), and hospital-acquired pneumoniae (HAP) 19% (21/109). After multivariable analysis, the following variables were significantly associated with LRTIs: age (OR 1.1, 95% CI 1.01–1.2), severe TBI (OR 2.7, 95% CI 1.1–6.9), AIS thorax (OR 1.4, 95 CI 1.1–1.8), and mechanical ventilation on admission (OR 3.7, 95% CI 1.1–13.5). At the same time, hospital mortality did not differ between groups (LRTI 18.6% vs. No LRTI 20.1%, p = 0.7), and ICU and hospital length of stay (LOS) were longer in the LRTI group (median [IQR] 12 [9–17] vs. 5 [3–9], p < 0.01) and (median [IQR] 21 [13–33] vs. 10 [5–18], p = 0.01), respectively. Time on the ventilator was longer for those with LRTIs. Conclusion The most common site/location of infection in patients with TBI admitted to ICU is respiratory. Age, severe TBI, thoracic trauma, and mechanical ventilation were identified as potential risk factors. LRTI was associated with prolonged ICU, hospital stay, and more days on a ventilator, but not with mortality.